The involvement of the dysfunctional insulin receptor signaling system in long COVID patients with diabetes and chronic pain and its implications for the clinical management using taVNS - Li, Riwang; Liu, Wenguo; Liu, Dahai; Jin, Xu; Wang, Shuxing (Frontiers in Pain Research, 2024)
In clinical terms, chronic pain is the most prevalent sequela resulting from COVID-19, which is induced by the novel coronavirus (SARS-CoV-2), while type 2 diabetes mellitus (T2D) is the most common comorbidity. This triangular relationship can be attributed to the dysfunction of the insulin receptor signaling system (IRSS) in both central and peripheral systems. Patients with T2D are essentially more susceptible to SARS-CoV-2 infection due to the widespread expression of angiotensin converting enzyme 2 (ACE2) in their pancreatic beta cells, which serves as the cellular port for the SARS-CoV-2 to infect and enter the cell. This infection can exacerbate chronic pain and insulin resistance for various reasons. Peripherally, once infected, the virus can cause damage to peripheral nerves and pancreatic β-cells, further exacerbating pain and glucose metabolism conditions. Additionally, in the central nervous system, dysfunctional IRSS is closely linked to chronic pain. Over the past few years of the COVID-19 pandemic, an increasing body of evidence suggests that insulin and other medications currently used in clinical practice for hyperglycemia control may not be safe for treating these patients. Therefore, we need a proper approach for the treatment of chronic pain in long COVID patients, especially patients with T2D. This review presents evidence that transcutaneous auricular vagal nerve stimulation (taVNS) may provide a viable treatment option for chronic pain and metabolic dysfunction by improving the function of IRSS in both the central nervous system and peripheral tissues.